Design-build subsurface projects - Brierley, Gary S.; Corkum, David H., 1954-; Hatem, David (Society for Mining, Metallurgy, and Exploration, 2010)
Design-Build Subsurface Projects, Second Edition, can help guide owners, engineers, construction managers, and contractors implement the Design-Build system. This cutting-edge book provides a straightforward, comprehensive look at how to make Design-Build work on complicated projects involving tunnels, highways, dams, and deep foundations.